EFEKTIVITAS E-LKPD BERBANTUAN LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Hanny Firtsanianta; Imroatul Khofifah (PROCEEDING UMSURABAYA, 2022)
Liveworksheet is a platform that helps teachers make electronic LKS or student activity sheets, commonly known as E-LKPD. Apart from its attractive appearance, this live worksheet is easy to use. LKPD serves to link teaching and learning activities so that there is effective interaction between students and teachers, which can increase student activities to improve academic achievement. This study aims to identify the improvement of student learning outcomes by using the E-LKPD live worksheet. This research method uses qualitative research methods with descriptive analysis techniques combined with library research, namely using various supporting literature references in the data collection process without going into the field. This type of research is qualitative research.Â Keywords: effectiveness; liveworksheet; learning outcomes